Formulation and Characterization of Alginate Coated Chitosan Nanoparticles as Therapeutic Protein for Oral Delivery System - Fitriagustiani, Fitriagustiani; Mustopa, Apon Zaenal; Budiarti, Sri; Warsito, Mega Ferdina; Pratiwi, Riyona Desvy; Agustiyanti, Dian Fitria; Nurfatwa, Maritsa (Trends in Sciences, 2022)
Nanoparticles have been promptly studied and developed for oral protein delivery. Selection of excipients and formulation method depends on the physicochemical characteristics of the protein carried. Therefore, this study aims to design a formulation and characterize the alginate coated chitosan nanoparticles which carried different protein. Alginate coated chitosan nanoparticles were formed using an ionic gelation method. Optimization was done by varying the parameter such as crosslinker concentration, agitation method, rate, and time. The results show that chitosan nanoparticles formed by sonication using sodium tripolyphosphate (STPP): chitosan (1:0.8) was the best method to form nanoparticles. The particle size and polydispersity index (PDI) of bovine serum albumin (BSA) and lysozyme nanoparticles were 812.2 nm and 0.412 for BSA while 793.3 nm and 0.438 for lysozyme. Encapsulation efficiency (EE) of BSA is 52 % and lysozyme is 68 %. In vitro tests on acidic/gastric conditions showed that lysozyme (±32 %) was released faster than BSA (±10 %) during the 24 h incubation. Under neutral/terminal intestine conditions, percentage of BSA (±17 %) release is slightly higher than lysozyme (±13 %) for 8 h incubation period. It was concluded that the formulation of alginate coated chitosan nanoparticles in this study appears to be more effective for BSA delivery than lysozyme. HIGHLIGHTS Nanoparticle vesicular system is an effective approach for protein drug delivery system Factors affecting the formation of chitosan nanoparticle are crosslinker concentration, agitation method, rate, and time Alginate coated chitosan nanoparticle was more effective for oral delivery of BSA compared to lysozyme GRAPHICAL ABSTRACT